High Prevalence of Genogroup I and Genogroup II Picobirnaviruses in Dromedary Camels - Jade L. L. Teng; Ulrich Wernery; Po Chun Wong; Elaine Chan; Hwei Huih Lee; Sunitha Joseph; Ru Bai; Ying Tang; Emily Y. M. Wong; Susanna K. P. Lau; Patrick C. Y. Woo (Viruses, 2021)
Picobirnaviruses (PBVs) are small non-enveloped bisegmented double-stranded RNA viruses found in humans, mammals, and birds. Increasing molecular epidemiology studies suggest a high sequence diversity of PBVs in numerous hosts and the environment. In this study, using 229 fecal samples from dromedary camels in Dubai, 52.8% were positive for PBVs, of which 77.7% and 41.3% were positive for genogroup I and II, respectively, and 19.0% were positive for both genotypes. Phylogenetic analysis showed high diversity among the sequences of genogroup I and II dromedary PBVs. Marked nucleotide polymorphisms were observed in 75.5% and 46.0% of genogroup I and II RNA-dependent RNA polymerase (RdRp) sequences, respectively, suggesting the co-existence of multiple strains in the same specimen. Both high genetic diversity and prevalence of genogroup I and II PBV in dromedaries were observed. In fact, the prevalence of genogroup II PBV in dromedaries is the highest among all animals to date. The complete/near-complete core genomes of five genogroup I and one genogroup II dromedary PBVs and partial segment 1 and 2 of both genotypes were also sequenced. The dromedary PBV genome organizations were similar to those of other animals. Genetic reassortment and mutation are both important in the ecology and evolution of PBVs.